CONGENITAL RUBELLA SYNDROME – CASE REPORT - Соболева, Мария Константиновна; Зорькина, Татьяна Владимировна; Богатырева, Александра Владимировна; Гребенкина, Ирина Владимировна; Протопопов, Владимир Владимирович (Mother and Baby in Kuzbass, 2017)
Case report had devoted to clinical observation and diagnistical process of congenital rubella syndrome (CRD) on newborn gerl. The presentation of congenital rubella syndrome consist the brain defect,nervus opticis atrophy,hearing impartment, vision impairment, fase bone defect and hypoplasia pinna and ear canal, hard and soft palate’s cleft on abnormality mediane line of face. Diadnosis of CDS was confirmed by PCR data and detected specific IgM and IgG antibody. For our opinion, this case CDS was result of mother’s rubella infection during 12 week of gravity.
Keywords: congenital rubella syndrom; presentation; diagnosis